Financial Enmeshment: Untangling the Web - Randy Kemnitz; Bradley Klontz; Kristy L Archuleta (Journal of Financial Therapy, 2016)
. Children learn through observing and interacting with their parents. Much of what children learn about money comes from these observations and interactions. An area of concern in parent – child relationships is the impact of boundaries and roles. Parents whose boundaries with their children are rigid and inflexible do not prepare their children to effectively deal with stress in their lives. Similarly, parents whose boundaries are too flexible may impede their children’s ability to develop appropriate coping skills. This is true of their development of personal finance, money, consumption, and debt coping skills. Financial enmeshment occurs when parents involve their children in adult financial matters before the children are cognitively and emotionally ready to cope with the information. Financial enmeshment may have a negative effect on the child’s development. Financial enmeshment can be addressed through financial therapy. This paper explores the dynamic of financial enmeshment and discusses tools available to financial professionals to help identify the dynamic and structure interventions.
Keywords: enmeshment; financial enmeshment; family systems; family structure